Double dens invaginatus in an impacted molariform supernumerary tooth: An unique case - Anegundi R; Kaveri H; Patil Shruthi; Punnya A (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2008)
Dens invaginatus is a relatively rare developmental anomaly affecting usually the permanent maxillary lateral incisor. Various factors have been put forward regarding its pathogenesis. Involvement of crown/root has been reported as the coronal and radicular variety of dens invaginatus. One of the rarest variant is the Double dens invaginatus and only a few cases have been reported in the literature.This article focuses on a case of double dens invaginatus in an impacted maxillary anterior supernumerary tooth, the associated complications and its management